Thoughts on Universalism versus Cultural Relativism, with Special Attention to Women’s Rights - Lakatos, István (Pécs journal of international and European law, 2018)
In light of the fact that recently cultural differences, the challenges of peaceful coexistence among people coming from different cultural background or even references to the existence of parallel societies in certain European cities are monopolizing the public discourse in many countries, it is important to analyse one of the oldest legal discussions about universalism versus cultural relativism. The article seeks to introduce the most important elements of this debate, which started with the adoption of the UN Universal Declaration of Human Rights. The paper demonstrates the discrepancy between the tendencies regarding the academic discussion and the approach by states on culturally sensitive issues. While scholars are taking more nuanced positions recently by acknowledging both the merits of universal human rights projects and the significance of culture in the conceptualization and implementation of human rights, the intergovernmental debates at different UN fora are still characterized by radical universalist and cultural relativists statements by member states as it was demonstrated during the first two cycles of the UPR discussion on women’s rights. A special focus was devoted to women’s rights as they are considered to be one of the culturally most sensitive ones and most affected by local traditions and practices.